Herbal Medicines and Recent Development on Novel Herbal Drug Delivery System - Ahmed, Aziz; Shuaib, Mohd; Shirsat, Mrunal K.; Sharma, Deeksha (Talenta Publisher, 2023)
The World Health Organization (WHO) defines herbal medicine as a technique that uses herbs, herbal ingredients, herbal preparations, and finished herbal products. Herbal remedies contain a variety of chemical components known as phytochemicals, which fall into a number of categories including saponins, flavonoids, glycosides, tannins, alkaloids, and terpenoids. Due to the presence of these phytochemicals, herbal medications can be used to treat a variety of ailments and diseases, including gastrointestinal problems, skin infections, arthritis, migraines, and weariness. Herbal medicines have less major adverse effects than conventional pharmaceuticals and are less expensive. New herbal formulations can include transfersomes, ethosomes, microspheres, phytosomes, liposomes, polymeric nanoparticles, and nanocapsules. In comparison to traditional herbal medicines, the novel herbal drug delivery systems offer many advantages, including increased solubility and bioavailability, protection from side effects, enhanced pharmacological action, increased stability, better delivery to tissue macrophages, consistent delivery, and protection against the physical and chemical breakdown of active ingredients. To incorporate standardised herbal extract or aqueously soluble active ingredients into phospholipids to build lipid companionable molecular complexes, phytosome has been described as a patented innovative herbal technology produced by a leading manufacturer of medicines and nutraceuticals. The use of herbal medicines can be expanded in order to increase their efficacy by incorporating them into more sophisticated medications.